Bitter and sweet taste threshold, body mass index and food preferences of Filipino young adults - Besana, Marivic Pascual
ABSTRACT The study aimed to determine the correlation of bitter and sweet taste thresholds with the body mass index (BMI) and food preferences of Filipino young adults. Fifty-five respondents, aged 20 to 35, classified according to their (BMI), were asked to answer a food preference checklist using a 9-point hedonic scale. Bitter and sweet taste recognition thresholds were determined by evaluating eight varying concentrations of taste solutions using the 3-Alternative Forced Choice (3-AFC) Method. Significant differences (p<0.05) were obtained between sweet and bitter food preferences only among the youngest respondents (20-25y.o) but did not vary across age. On the other hand, prefereces for fruits were significantly (p<0.05) affected by sex. Vegetable preferences had significant (p<0.05) differences across BMI classifications while beverages had the lowest mean preference scores within all BMI classifications. Correlation analysis revealed that sweet and bitter taste thresholds did not show association with BMI. Sweet taste thresholds was positively correlated (p<0.05) with milk and dairy products. Individual correlation showed that fruit juice and kakanin preferences had negative (p<0.05) associations with both sweet and bitter taste thresholds, and sweet taste threshold alone, respectively.